Spatially Distribution of Soil Ultimate Bearing Capacity at Singkil-Aceh Based on a Static Cone Penetration Test - Halida Yunita; Nafisah Al Huda; Devi Sundary; Hendra Gunawan; Munira Sungkar; Bambang Setiawan; Dewi Sartika (Aceh International Journal of Science and Technology, 2022)
The Singkil Sub-district of Aceh Singkil District comprises alluvium deposits with a relatively low ultimate bearing capacity. The ultimate bearing capacity of the soil is closely related to the safety of a building. The important thing related to estimating the ultimate bearing capacity of the soil is in-situ soil investigation. This study aims to estimate the spatial distribution of soil ultimate bearing capacity using field test data in the Singkil Sub-district. Estimating ultimate bearing capacity is useful to provide an initial picture for various planning and infrastructure development activities in the study area. Twenty CPT in-situ tests have been obtained from various field works in Aceh Singkil Regency. Field data analysis, based on empirical methods, was carried out to obtain the value of the ultimate bearing capacity of the soil at the test location. Then, the estimated distribution of the maximum bearing capacity obtained was carried out. The zoning map of the distribution of soil ultimate bearing capacity in the study was developed from this research. This map can be used as a form or effort of disaster mitigation by various stakeholders involved in planning and building various infrastructure facilities in the Singkil Sub-district